Are the single-step resection and primary anastomosis suitable for obstructıve colorectal patients in older cases? - Selcuk Kaya; Onder Altin; Yunus Emre Altuntas; Metin Kement; Levent Kaptanoglu; Ahmet Seker; Nejdet Bildik; Hasan Fehmi Kucuk (Medicinski glasnik, 2018)
Aim: To investigate the efficacy and safety of the single-step surgery in elderly patients with obstructive colorectal cancer. Methods: All patients who underwent single-step surgery and primary anastomosis for obstructive colorectal cancer in the period between January 2012 December 2017 were evaluated in this study. The patients were divided into two groups: younger than 65 (Group Young) and older than 65 (Group Old). Demographic data, American Society of Anesthesiologists scores (ASA) scores, comorbidities, preoperative albumin levels, type of surgery, postoperative morbidity and mortality, pathological stages, and overall survival rates were investigated. Results: A total of 89 patients were included: 49 (54%) were older than 65 (Group Old). In Group Old, the mean age was 75 (65-97), of which 28 (58.3%) were males. There were 41 patients younger than 65 (Group Young) with the mean age of 52.6 (41-64 years of age), of which 21 (51.2%) were males. There was no difference between groups according to albumin level. There was no statistical difference between two groups according to tumour localization, pathological stage and type of surgery, as well as according to surgical complications. The median overall survival rate was 11 months in both groups (0-66) (p=0.320). Conclusion: Meticulous preparation of older patients (correction of anaemia, electrolyte levels and pH) paves the road for successful surgeries, including single-step resection and primary anastomosis.
Keywords: anastomosis; colorectal surgery; surgical